2021
DOI: 10.1002/jssc.202001163
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐allergic compounds screened from Shengmai injection by using high‐expression Mas‐related G protein‐coupled receptor X2 cell membrane chromatography online coupled with liquid chromatography and mass spectrometry

Abstract: Adverse drug reactions of traditional Chinese medicine injection mainly manifested as pseudo‐allergic reactions. In the present study, ginsenoside Rd, Ro, and Rg3 were identified as pseudo‐allergic components in Shengmai injection by a high‐expression Mas‐related G protein‐coupled receptor X2 cell membrane chromatography coupled online with high‐performance liquid chromatography and mass spectrometry. Their pseudo‐allergic activities were evaluated by in vitro and in vivo assay. The three compounds were furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Exogenous ligands of MRGPRX2 include the cationic polymer compound 48/80 (C48/80), which is commonly used in receptor functional assays, and a variety of drugs approved by the Food and Drug Administration (FDA), such as fluoroquinolones (e.g., ciprofloxacin), neuromuscular blocking agents (e.g., rocuronium, atracurium), opioids (e.g., morphine), and many others [ 4 , 9 , 28 ]. MRGPRX2 can also be activated or inhibited by other exogenous agents, such as bacterial quorum sensing proteins, insect venoms [ 3 , 29 , 30 ], or many different plant xenobiotics ( Figure 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; representatives of which are described in the following part of this review.…”
Section: Pathophysiological Basismentioning
confidence: 99%
“…Exogenous ligands of MRGPRX2 include the cationic polymer compound 48/80 (C48/80), which is commonly used in receptor functional assays, and a variety of drugs approved by the Food and Drug Administration (FDA), such as fluoroquinolones (e.g., ciprofloxacin), neuromuscular blocking agents (e.g., rocuronium, atracurium), opioids (e.g., morphine), and many others [ 4 , 9 , 28 ]. MRGPRX2 can also be activated or inhibited by other exogenous agents, such as bacterial quorum sensing proteins, insect venoms [ 3 , 29 , 30 ], or many different plant xenobiotics ( Figure 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; representatives of which are described in the following part of this review.…”
Section: Pathophysiological Basismentioning
confidence: 99%
“…Cellular membrane affinity chromatography (CMAC) has been considered a desirable technique for identifying the interaction between membrane ligands and receptors. , This interaction assay plays an essential role in drug research. For instance, CMC has attracted tremendous attention in the field of screening active ingredients from natural products, and MS can be used to further analyze the detailed structure of the eluted compounds. A previous study suggested that the analyte activity was in good relation with the retention property in CMC. Pancreatic islet cell membranes from a mouse were coated onto the capillary inner surface .…”
Section: Microscale Systems “See” In Cellsmentioning
confidence: 99%
“…Many small molecule drugs, such as fluoroquinolones, and cationic amphiphilic drugs can dose-dependently induce PAR [2,3]. Some traditional Chinese medicine injections are also the culprit of PAR [4][5][6]. Recently, pseudo-allergic adverse reactions have been demonstrated to be induced through the activation of Mas-related G protein-coupled receptor-X2 (MrgX2) [2], which is a class A G proteincoupled receptor (GPCR) expressed in mast cells (MCTC subtypes).…”
Section: Introductionmentioning
confidence: 99%